Implications of the Space Agreement; A Critique of the Statement of the American President to Exploit Space Resources - Athari Farhani (ADALAH, 2020)
Abstract:As the world’s population grows increasing demand for the planet’s limited resources, developed countries begin to explore outer space. One of them is the United States through its president statement Donald Trump who will explore and exploit space resources. While the law of space including natural resources contained therein is a shared heritage of mankind. And whether said activities comply with the current provisions of internaional space law?Keyword:  Outerspace, natural resources, mining, heritage of mankind